Rancangan Pembelajaran Gerak Makhluk Hidup Melalui Model Pembelajaran Inkuiri dan Literasi Sains - Alberida, Heffi; Arsih, Fitri; Helendra, Helendra; Fadilah, Muhyiatl (JURNAL EKSAKTA PENDIDIKAN (JEP), 2017)
The aims of this research are to result valid and practice student texs book bases on inquiry and science literate for junior High School. This research used Plomp Models: a preliminary investi-gation (preliminary research), stage of development or prototype creation stage (development or pro-totyping phase), and the stage of assessment (assessment phase). The subject research were thirty stu-dents from Juniorr High School 12 Padang. Data is primary data collected directly from validation and practicality questionnaires. Data analyze descriptively statistic. The result shows that student texs book have 89,29%, in validity and 86,57% in practicality by teachers and 83,72% in practicality by students. It can conclude that student texs book bases on inquiry and science literate have valid and practice to use in learning.